2014
DOI: 10.2337/dc13-1634
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Type 1 Diabetes Cardio-Renal Intervention Trial (AdDIT): Urinary Screening and Baseline Biochemical and Cardiovascular Assessments

Abstract: OBJECTIVEWe assessed the association between early increases in albumin excretion and cardiovascular (CV) and renal markers in a large cohort of young people with type 1 diabetes. RESEARCH DESIGN AND METHODSAs part of preliminary screening for a multicenter, randomized controlled trial of statins/ACE inhibitors, we measured albumin-creatinine ratio (ACR) in six early morning urine samples from 3,353 adolescents (10-16 years of age) and calculated tertiles based on an established algorithm. From those subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 47 publications
1
65
0
Order By: Relevance
“…The multicenter Adolescent Type 1 Diabetes Cardio-Renal Intervention Trial (AdDIT) (n 5 3,353, age 10-16 years) used ACR to assign risk: those in the highest tertile were treated with ACE inhibitors and statins, while those in the middle and lower tertiles were observed. Vascular measurements, kidney disease markers, and cardiovascular markers demonstrated that youth in the highest tertile had more rapid decline in kidney and cardiovascular function despite treatment; however, those in the lower-risk groups also showed evidence of endothelial dysfunction, suggesting that ACR is a continuous risk factor for kidney and cardiovascular dysfunction (160). Another study in youth with type 1 diabetes (age .11 years, mean 14 years; mean A1C 8.3%; .2-year duration, mean 6.3 years) found that 16.1% already had moderately increased albuminuria, 30.3% had dyslipidemia, and 12.3% had hypertension (161).…”
Section: New-onset Diabetes After Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…The multicenter Adolescent Type 1 Diabetes Cardio-Renal Intervention Trial (AdDIT) (n 5 3,353, age 10-16 years) used ACR to assign risk: those in the highest tertile were treated with ACE inhibitors and statins, while those in the middle and lower tertiles were observed. Vascular measurements, kidney disease markers, and cardiovascular markers demonstrated that youth in the highest tertile had more rapid decline in kidney and cardiovascular function despite treatment; however, those in the lower-risk groups also showed evidence of endothelial dysfunction, suggesting that ACR is a continuous risk factor for kidney and cardiovascular dysfunction (160). Another study in youth with type 1 diabetes (age .11 years, mean 14 years; mean A1C 8.3%; .2-year duration, mean 6.3 years) found that 16.1% already had moderately increased albuminuria, 30.3% had dyslipidemia, and 12.3% had hypertension (161).…”
Section: New-onset Diabetes After Transplantationmentioning
confidence: 99%
“…After adjusting for completeness of ascertainment, recent reports on the increasing incidence of Optimal care for patients with DKD is complex and best managed using comprehensive multifactorial risk-reduction strategies (160,161). There is a growing consensus that patient outcomes are most improved with simultaneous control of BP, glucose, and lipids; use of antiplatelet agent therapy when indicated; and lifestyle modifications that include smoking cessation, a healthy diet, exercise, and weight reduction among those who are overweight or obese (4,20).…”
Section: Treatment Of Hypertension and Dkdmentioning
confidence: 99%
“…Samples were stored at -708C before shipping. Urine albumin was measured using laser immunonephelometry (Siemens BN Prospec) and for concentrations ,2.1 mg/L by an ELISA (14). Urine creatinine was measured using a chromatographic stable isotope dilution electrospray mass spectrometry-mass spectrometry method.…”
Section: Methodsmentioning
confidence: 99%
“…The data from randomized, clinical trials such as the TODAY study in youth with T2D 60 and those anticipated from the Adolescent Type 1 Diabetes Cardio-Renal Intervention Trial (AdDIT) study in youth with T1DM will begin to provide much-needed data on the management of CVD risk factors in diabetes mellitus. 412 Participants in TODAY were treated for hypertension and dyslipidemia per study protocols, and although these were not the primary study aims, these longitudinal data will inform the management of these CVD risk factors in youth with T2DM. Similarly, the AdDIT study should soon provide data on the use of statins and angiotensin-converting enzyme inhibitors in adolescents with T1DM.…”
Section: Gaps In Knowledgementioning
confidence: 99%